Study on concordance of ictal and interictal epileptiform activity in patients with tuberous sclerosis complex - Yang, Zhixian (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2014)
OBJECTIVE: To analyze the relationship between the ictal onset zone and dominant interictal epileptiform foci in tuberous sclerosis complex (TSC) patients